The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1039/c2gc35503e
|View full text |Cite
|
Sign up to set email alerts
|

Efficient catalytic hydrogenation of levulinic acid: a key step in biomass conversion

Abstract: γ-Valerolactone (GVL) has been proposed as a sustainable liquid, and could be used for the production of hydrocarbons by using both homogeneous and heterogeneous catalytic systems. The selective reduction of levulinic acid (LA) to GVL is a key transformation for biorefinery concepts based on platform molecules. We report a detailed investigation of the conversion of LA to GVL using molecular hydrogen in the presence of a catalyst in situ generated from Ru(acac) 3 , and electronically and sterically characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
79
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(83 citation statements)
references
References 57 publications
(51 reference statements)
4
79
0
Order By: Relevance
“…Among the platform molecules levulinic acid could play a key role in the chain [43], since it is the raw material of a proposed platform chemical (gamma-valerolactone) that can be obtained by its selective hydrogenation [44][45][46][47][48]. Extending the queue a new product, biopolymer generation was established by Tanamool [49] at laboratory scale.…”
Section: Introductionmentioning
confidence: 99%
“…Among the platform molecules levulinic acid could play a key role in the chain [43], since it is the raw material of a proposed platform chemical (gamma-valerolactone) that can be obtained by its selective hydrogenation [44][45][46][47][48]. Extending the queue a new product, biopolymer generation was established by Tanamool [49] at laboratory scale.…”
Section: Introductionmentioning
confidence: 99%
“…of tertiary sulfonated phosphines without using any solvent or additive with TOF = 1440-3538 s −1 . 18 It should be noted that this system was also found to be active under continuous conditions. 19 During the decomposition of carbohydrates, LA and formic acid are formed in equimolar amounts.…”
mentioning
confidence: 99%
“…For the selective conversion of LA to GVL, the highest activity of the Ru catalyst modified with a monodentate phosphine ligand was achieved by applying Bu-DPPDS under 100 bar H 2 at 140°C (Table 1, entry 2). 18 It was revealed that the hydrogenation activity of the Ru catalysts can be significantly enhanced by the use of chelating-type bidentate Ph 2 P(CH 2 ) n PPh 2 (n = 1-3) ligands. 23 Thus, we compared the activity of a Ru catalyst modified with Ph 2 P(CH 2 ) 4 PPh 2 (Scheme 1, DPPB), a Bu-DPPDS analogue, for the reduction of LA.…”
mentioning
confidence: 99%
“…[41] Sulfonation of these ligands enhances both their solubility in polar solvents and also minimises their vapour pressure making them easier and safer to handle. Catalysts were generated in situ via reaction with Ru(acac) 3 , and catalysis performed at 100 bar H 2 , 140 o C. The steric and electronic properties of the phosphine ligands had significant influence on the activity of the catalysts.…”
Section: Hydrogenation Of Levulinic Acid (La) To γ-Valerolactone (Gvl)mentioning
confidence: 99%